The Mediating Role of Job Satisfaction in the Relationship between Emotional Intelligence and Life Satisfaction among Teachers during the COVID-19 Pandemic - Aleksandra M. Rogowska; Hanna Meres (MDPI AG, 2022)
This study examines the indirect effect of job satisfaction on the relationship between emotional intelligence and life satisfaction among teachers during the second wave of the COVID-19 pandemic in Poland. A sample of 322 teachers aged 23-71 (M = 45.37, SD = 8.99) participated in a cross-sectional online survey. The online survey (Google form) contained some demographic information and standardized psychological questionnaires: the Multivariate Emotional Intelligence Scale (MEIS) for measuring emotional intelligence, the Minnesota Satisfaction Questionnaire (MSQ)-a short form for job satisfaction assessment, and the Life Satisfaction Scale (SWLS). Emotional intelligence is a significant positive predictor of job satisfaction and life satisfaction, and job satisfaction is a strong positive predictor of life satisfaction. Job satisfaction partly mediates the relationship between emotional intelligence and life satisfaction. To maintain the well-being of teachers during a pandemic, schools should implement training to improve emotional intelligence and increase job satisfaction by supporting distance e-learning among teachers.